2015
DOI: 10.12968/jowc.2015.24.8.388
|View full text |Cite
|
Sign up to set email alerts
|

Danish translation and validation of the International Skin Tear Advisory Panel Skin Tear Classification System

Abstract: The ISTAP Skin Tear Classification System was developed with the goal of establishing a global language for describing and documenting skin tears and to raise the health-care community's awareness of skin tears. The Danish translation of the ISTAP classification system supports the earlier ISTAP study and further validates the classification system. The Danish translation of the classification system is vital to the promotion of skin tears in both research and the clinical settings in Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…The ISTAP Skin Tear Classification System includes three skin tear types: no skin loss, partial skin loss, or complete skin loss (Figure A). The system was developed in English and has been translated into Danish and validated . LeBlanc et al (2018) report that the translation and validation of the system is underway in French, Italian, Chinese, Portuguese, Spanish, and Czech (Personal correspondence with Kimberly LeBlanc, February 29, 2018).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ISTAP Skin Tear Classification System includes three skin tear types: no skin loss, partial skin loss, or complete skin loss (Figure A). The system was developed in English and has been translated into Danish and validated . LeBlanc et al (2018) report that the translation and validation of the system is underway in French, Italian, Chinese, Portuguese, Spanish, and Czech (Personal correspondence with Kimberly LeBlanc, February 29, 2018).…”
Section: Introductionsupporting
confidence: 91%
“…In the present study, a moderate agreement among RNs and non‐RNs was found. The results of this study support those reported by LeBlanc et al and Skiveren et al LeBlanc et al reported a substantial level of agreement among the ISTAP panel members in their study, which was attributed to the extensive knowledge that the panel as a collective has on skin tears. Achieving moderate agreement for the ISTAP skin tear tool in this study is an important milestone as it demonstrates the validity of the tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2014, there were no Danish studies or guidelines on skin tears. Since then, the International Skin Tear Advisory Panel (ISTAP) has been translated into Danish and validated (12), and a prevalence study in a Danish nursing home has been undertaken. That study, of 128 residents, showed a prevalence of 4⋅6% (13).…”
Section: Key Messagesmentioning
confidence: 99%
“…With the adaptation of the ISTAP Skin Tear Classification, Brazil joins Denmark, Sweden, Italy, and Canada, with cultural adaptations in French and English . The first country to adapt the classification system was Denmark, which, like the original study, used the 30 photograph database to validate the instrument. This study was performed with a sample of 270 professionals from the health area (241 nurses) and obtained a moderate concordance ( k = 0.46), similar to the original study .…”
Section: Discussionmentioning
confidence: 99%